NUMERICAL SIMULATION FOR SEASONAL AND INTER-ANNUAL CHANGE OF DISSOLVED OXYGEN IN LAKE BIWA, JAPAN (GEOMATE Journal, 2020)
The dynamics of dissolved oxygen in lake is a fundamental issue of comprehending the water environmental habitats of aquatic organisms. In recent years, the decrease in dissolved oxygen has been observed at the bottom of the northern part of Lake Biwa, Japan. In recent years, eutrophication and global warming caused the decrease in the dissolved oxygen in the deep layer. Under these circumstances, in order to preserve the ecosystem of Lake Biwa and to provide water resources, the environmental changes in Lake Biwa should be accurately grasped. In our present study, a water quality model considering the flow field from hydrodynamic model was developed in order to grasp the concentration of phytoplankton, zooplankton, nitrogen, phosphorus, dissolved oxygen and chemical oxygen demand in Lake Biwa. Numerical simulation was carried out for 3 years from 2007 to 2009. Comparisons of the simulations with the observations showed that the seasonal and interannual change of dissolved oxygen was well reproduced. The dissolved oxygen decreased during decomposingthe organic matter by bacteria in the bottom layer with little oxygen supply from the atmosphere and the photosynthesis from the phytoplankton under the thermocline from spring to autumn. The simulation confirmed that in each year, the dissolved oxygen was supplied in all layers by the overturning in winter.